If (x+3) divides x^2+kx+12 then k
Answers
Answered by
2
Answer:
Step-by-step explanation:
That means:
x = -3
We know by factor theorem that if the remainder is zero, the expression divides the other expression perfectly.
So,
f(x) = x^2 + kx + 12
f(-3) = 9 - 3k + 12
We know that f(-3) = 0; since (x+3) perfectly divides f(x).
So,
-3k + 9 + 12 = 0
-3k = -21
k = -21/-3
k = 7
I hope this helped!!
Regards,
Lilac584
Similar questions
Social Sciences,
1 month ago
English,
1 month ago
Hindi,
2 months ago
English,
2 months ago
Accountancy,
11 months ago
Biology,
11 months ago
Physics,
11 months ago